Potential of Robusta Coffee Bean Extract (Coffea canephora) Peaberry Roasted and Green Bean Pagar Alam City against the Growth of Candida albicans Fungus - Yunilda Rosa; Riyanto Riyanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
A type of coffee plant that is widely cultivated in the city of Pagar Alam, South Sumatra is Robusta coffee (Coffea canephora). The robusta coffee plant is one of the traditional plants that can be used as a medicine. The purpose of this research is to analyze the potential of Robusta peaberry Sangrai coffee bean extract and green bean from Pagar Alam city against the growth of Candida albicans fungus. The test method is carried out by extraction, phytochemical screening test and anti-fungal activity test of Robusta coffee bean extract. The results of testing antifungal activity showed that ethanol extracts of roasted peaberry robusta coffee beans and green bean can inhibit the growth of C. albicans fungi by forming clear zones. Secondary metabolite compounds contained in roasted peaberry robusta coffee bean extract and green bean are alkaloids, flavonoids, tannins, saponins and terpenoids. The minimum inhibitory content (MIC) of ethanol extract of roasted peaberry robusta coffee beans and green bean against the growth of C. albicans fungus in vitro is at a concentration of 10%. Based on the results of research on ethanol extract, roasted peaberry robusta coffee beans and green bean have the potential to be anti-fungal because they can inhibit the growth of C. albicans fungus.